Predictors of time to diagnosis of Huntington disease patients followed up at a specialized healthcare institution in Peru - Silva-Bullon, Midiam (2026)
Objective: This study analyzes the predictors with time to diagnosis (TTD) in Huntington’s disease (HD) patients treated at a specialized institute in Peru. Materials and Methods: Retrospective cohort study with review of clinical records and prospective application of a questionnaire (February 2024-February 2025) to 130 individuals over 18 years old with a molecular diagnosis of HD, treated at a specialized institute. Demographic, clinical, and some social determinants of health predictors were analyzed using multivariate linear regression to identify those associated with the time to HD diagnosis. Results: The mean TTD, from the first symptom to the genetic diagnosis was 5.8 ± 5.7 years. HD individuals whose first medical care was at a local/regional hospital, a higher number of physicians involved, public health insurance, being retired or dedicated to household tasks, as well as age (at first symptom, clinical diagnosis, and genetic diagnosis) showed a statistically significant association as predictors of TTD, regardless of sex, years of education, health insurance, employment, age at first symptom, or delay due to COVID-19. Conclusions: The type of healthcare facility initially consulted, a higher number of physicians involved in the diagnosis, certain employment conditions, and the ages at first medical care and diagnosis suggest the need to improve the quality and accessibility of healthcare services involved in the management of HD.